[RETRACTED ARTICLE] Business Strategies for a Variety of Changes to Achieve Competitiveness with the World - Jaemjarus, Narodom (Journal of Dhamma for Life, 2025)
The objective of this research is to understand how organizations share knowledge and, in particular, the role of rewards and social units in knowledge transfer in multicultural contexts. We wanted to examine how knowledge is shared and determine possible incentives and barriers to knowledge sharing in the integration of diverse cultures in the UAE. Use quantitative research methods. The study population included first-level managers in Dubai, UAE. The variables in the study were knowledge sharing (y), and each independent variable (xi) was financial award, social unit, and multiculturalism. Analyze data using descriptive statistics The results of the research showed that the first research question the vacant hypothesis is rejected, which indicates a positive and rewarding relationship for knowledge sharing and knowledge sharing behavior in multicultural organizations. The second empty hypothesis is not rejected. Indicates that there is insufficient data to select alternative hypotheses over empty hypotheses (e.g., data does not indicate a positive correlation between members of managers in social units and knowledge sharing with fellow members of the organization) The third empty hypothesis is also not rejected. It states that there is insufficient data to conclude that there is a positive correlation between the cultural diversity of the organization and the sharing of knowledge within the organization. The findings also reveal a positive correlation between the sum of the awards. Social Unit and Cultural Diversity and Knowledge Sharing Understanding the Determinants of Knowledge Sharing Behavior in Multicultural Organizations It will help to design a better knowledge-sharing system in this context.